42.4k views
5 votes
If f(x) = square root of x+3, what is the equation for f–1(x)? f–1(x) = x2 - 3 f–1(x) = x2 + 3 f–1(x) = (x - 3) 2 f–1(x) = (x + 3) 2

1 Answer

2 votes

Answer:


\Large \boxed{\sf \ \ f^(-1)(x)=x^2-3 \ \ }

Explanation:

Hello,


\text{For }x+3\geq 0\\\\f(x)=√(x+3)\\\\x=(fof^(-1))(x)=f(f^(-1)(x))=\sqrt{f^(-1)(x)+3}\\\\\text{*** take the square ***}\\\\f^(-1)(x)+3=x^2\\\\\text{*** subtract 3 from both sides ***}\\\\\large \boxed{\sf \ \ f^(-1)(x)=x^2-3 \ \ }\\

Hope this helps.

Do not hesitate if you need further explanation.

Thank you

User Geerten
by
4.7k points